2022
DOI: 10.1155/2022/1322826
|View full text |Cite|
|
Sign up to set email alerts
|

Automatic Detection of Epilepsy Based on Entropy Feature Fusion and Convolutional Neural Network

Abstract: Epilepsy is a neurological disorder, caused by various genetic and acquired factors. Electroencephalogram (EEG) is an important means of diagnosis for epilepsy. Aiming at the low efficiency of clinical artificial diagnosis of epilepsy signals, this paper proposes an automatic detection algorithm for epilepsy based on multifeature fusion and convolutional neural network. Firstly, in order to retain the spatial information between multiple adjacent channels, a two-dimensional Eigen matrix is constructed from one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The results have shown the perfect Sen scores for most subjects except for a few (2–7) subjects out of 24. A tremendous performance improvement was observed in some studies if these subjects were excluded [ 44 , 45 , 47 ]. It is very challenging to achieve outstanding performance in this study setting for the following reasons, which coincide with the main contributions of this study:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results have shown the perfect Sen scores for most subjects except for a few (2–7) subjects out of 24. A tremendous performance improvement was observed in some studies if these subjects were excluded [ 44 , 45 , 47 ]. It is very challenging to achieve outstanding performance in this study setting for the following reasons, which coincide with the main contributions of this study:…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the previous studies discarded the records with no seizure events in them, even though those records are part of the continuous EEG signal. Some studies even considered a portion of the data or excluded some based on their choice for analysis [44][45][46][47][48]. When the data are balanced for testing or portions of data are left out of consideration in the analytical process, this can greatly impact the performance score.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%